The Addition Of Bilateral Neurodynamics In Ultrasound Therapy And Manual Traction Intervention In Cervical Radiculopathy - Made Hendra Satria Nugraha; Gede Parta Kinandana (Jurnal Keterapian Fisik, 2022)
Background: Cervical radiculopathy is a condition that characterized by pain and/or sensorimotor deficits caused by compression of one or more cervical nerve roots. The aim of this case series is to serve as a preliminary study to determine the effectiveness of adding bilateral neurodynamics to the intervention of ultrasound therapy and manual traction in cervical radiculopathy. Methods: The research writing method used CARE (CAseREport) guidelines, which consisted of: introduction, patient information, clinical findings, timeline, diagnostic assessment, therapeutic intervention, follow-up and outcome, and discussion. The measuring instrument used in this study was the Visual Analogue Scale (VAS) in assessing tension pain when given neurodynamics and neck disabilities using the Indonesian version of the Neck Disability Index (NDI). The intervention was carried out 12 times (3 times a week for 4 weeks) and a follow-up was done at week 5. Results: The results showed that there was an improvement in the score of neck pain and disability in the 2 patients both at post-test and at follow-up. Conclusion: Based on these findings, it can be concluded that the application of additional bilateral neurodynamics in the intervention of ultrasound therapy and manual traction can help reduce pain and improve neck disability.